Range Expansion of Dermacentor variabilis and Dermacentor andersoni (Acari: Ixodidae) Near Their Northern Distributional Limits. Issue 3 (28th November 2014) - Dergousoff, Shaun J.; Galloway, Terry D.; Lindsay, L. Robbin; Curry, Philip S.; Chilton, Neil B.
Abstract : Distributional ranges of the ticks Dermacentor andersoni Stiles and Dermacentor variabilis (Say) in the Canadian Prairies were determined by passive surveillance and active collection. These findings were compared with historical records of both species, particularly in the province of Saskatchewan, where the northern distributional limits of both tick species occur. Before the 1960s, D. variabilis and D. andersoni were allopatric in Saskatchewan; however, since then, the distribution of D. variabilis has expanded westward and northward. Although the range of D. andersoni has remained relatively stable, range expansion of D. variabilis has resulted in a zone of sympatry at least 200 km wide. Twenty-nine species of mammals and three species of birds were identified as hosts for different life stages of these ticks.